Inhibition of Period Gene Expression Causes Repression of Cell Cycle Progression and Cell Growth in the Bombyx mori Cells - Qiu, Jian-Feng; Li, Xue; Cui, Wen-Zhao; Liu, Xiao-Fei; Tao, Hui; Yang, Kun; Dai, Tai-Ming; Sima, Yang-Hu; Xu, Shi-Qing (Frontiers in Physiology, 2019)
Circadian clock system disorders can lead to uncontrolled cell proliferation, but the molecular mechanism remains unknown. We used a Bombyx mori animal model of single Period gene (BmPer) expression to investigate this mechanism. A slow growing developmental cell model (Per-KD) was isolated from a B. mori ovarian cell line (BmN) by continuous knock down of BmPer expression. The effects of BmPer expression knockdown (Per-KD) on cell proliferation and apoptosis were opposite to those of m/hPer1 and m/hPer2 in mammals. The knockdown of BmPer expression led to cell cycle deceleration with shrinking of the BmN cell nucleus, and significant inhibition of nuclear DNA synthesis and cell proliferation. It also promoted autophagy via the lysosomal pathway, and accelerated apoptosis via the caspase pathway.